Outbreak of polycystic liver in red hybrid tilapia, Oreochromis niloticus (L.) x Oreochromis mossambicus (Peters) - Salihin, Mohamad Ismail (Japanese Society of Fish Pathology, 2016)
Polycystic lesions have been reported in many different fish species. This paper reports for the first time a case of polycystic lesions in the liver of tilapia. A group of 700 tilapia juveniles of approximately 50 g was obtained from a hatchery in Negeri Sembilan, Malaysia. When they were between 130 and 250 g, they started to show distended abdomen but appetite remained normal. Post-mortem examination on 30 randomly selected tilapia revealed numerous large masses containing jelly-like material in the peritoneal cavity of 33% of the fish. Histopathology revealed typical cystic lesion of liver tissue. This is the first report in hybrid tilapia and is presumed to be the result of a genetic anomaly.